The Effect of Mycotoxins Adsorbents Beta Glucans or Montmorillonite on Bovine Ruminal Fermentation In Vitro - Pozzo, Marcelo Dal; Viegas, Julio; Kozloski, Gilberto Vilmar; Stefanello, Cristiano Miguel; Silveira, Alisson Minozzo da; Bayer, Cimélio; Santurio, Janio Morais (Acta Scientiae Veterinariae, 2016)
Background: The addition of adsorbents in foods has been the strategy used by nutritionists to reduce the toxic effects of mycotoxins in animals. Mycotoxins are found in a range of foods and commonly they present variations in the chemical structure therefore, it has been appropriate to include adsorbents from different sources in the diet of ruminants. However, few researches were conducted in order to better understand the interaction of adsorbents on ruminal fermentation. Our objective in this study was to investigate the possible effects of two adsorbent products on bovine ruminal fermentation. One consists of 65% of β-glucan (β-glu), originating cell wall of Saccharomyces cerevisiae and used at a concentration of 1% and natural sodium montmorillonite (MMT) at a concentration of 5%. Materials, Methods & Results: The effects of β-glu adsorbents (1%) and MMC (5%) in culture medium that simulated ruminal fermentation were evaluated. Bottles, with a capacity of 120 mL, were used to be filled with substrate such as maize and ryegrass hay ground, nutrient solution (medium of Menke), liquid extracted rumen fistulated bovine and the two adsorbents evaluated, totaling 50 mL. The experiment was conducted with three treatments, named after: control (Cont), β-glu and MMT. In the control treatment adsorbents were not added. Six replicates were used for each treatment and two trials were conducted. One of the tests aimed to determine the fermentation kinetics by means of the gas production after 72 h’ incubation and quantifying the production of methane (CH4) at 48h. While another test aimed to quantify the production of short chain fatty acids (SCFA) - acetic, propionic and butyric acid - and the production of ammonia (NH3) in 24 h incubation. All assays were measured by gas chromatography. The highest total SCFA concentration was observed in β-glu treatment (67.71 mM) significantly superior to CONT (57.7 mM) treatment and MMT (53.28 mM), which was significantly lower than the β-glu treatment, but similar to CONT. The average representation (%) of acetic acid for the treatment MMT (62.9%) was significantly higher than the β-glu treatment (61.0%). The average proportions of propionic acid were similar between treatments, while the average representation (%) of butyric acid production was significantly higher for the β-glu treatment (13.1%) compared to CONT treatments (11.3%) and MMT (11.4%). The amount of NH3 was significantly reduced in MMT (9.6 mM) treatment compared to β-glu treatments (12.2 mM) and CONT (11.3 mM). In another test, the greater volume of gas (mL) was produced by β-glu treatment (103.4 mL), which was significantly greater than the treatments CONT (89.0 mL) and MMT (91.6 mL). The lag time, i.e. the time taken by the bacteria inoculum to develop lead-through in the substrate, in the MMT treatment took 6.2 h, slowing significantly compared to CONT treatments (4.8 h) and β Glu (4.33 h). The concentration of CH4 was significantly lower in MMT treatment (33.0%) compared to the CONT treatments (36.3%) and β-glu (35.68%). Discussion: The glucans which constitute the main cell wall S. cerevisae are the β-glucans with β-1-3 and β-1,6 glycosidic bonds. The largest and most significant concentration of SCFA and gas volume in the β-glu treatment can be explained by the degradation of β-glucans by rumen bacteria. The possible reason of reduced concentration of methane (CH4) in samples collected during 48 h of incubation in MMT treatment stands on the reduction in symbiotic activity of methanogenic bacteria and protozoa. Also, the possible reason of reduction in the concentration of ammonia (NH3) in MMT treatment could be associated to damage on protozoa with proteolytic activity. Our results showed that the amount of montmorillonite in rumen fluid influenced negatively the fermentative activity, therefore, delaying the colonization of bacteria in rumen substrate composed of maize and ryegrass hay. Moreover, the use of β-glu (1%) significantly increased the amount of short chain fatty acids such as, acetic acid and butyric acid, with the exception of propionic acid.